2020
DOI: 10.1111/jam.14923
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of copper ions against Mycobacterium avium subsp. paratuberculosis and bacterial communities in naturally contaminated raw cow’s milk

Abstract: Aim The focus of the present study was to evaluate the copper ions treatment on the viability of Mycobacterium avium subsp. paratuberculosis (MAP) and other bacterial communities in cow’s milk. Methods and Results A copper ions treatment was evaluated in naturally contaminated cow’s milk to assay MAP load and/or viability, and relative abundance of other bacterial communities. In addition, physical–chemical analyses of the milk were also performed. All analyses were carried out before and after a copper ions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 49 publications
(40 reference statements)
2
10
0
Order By: Relevance
“…Copper surfaces can eliminate bacterial pathogens, viruses and fungi (Faúndez et al 2004, Wilks et Recently, using an in vitro model, we showed that the use of a copper ions treatment protocol significantly reduced MAP load in PBS (Steuer et al 2018). Later, we observed that copper ions decreased viable MAP numbers in milk in a similar way (Steuer et al 2020). However, some MAP cells apparently either tolerate the effects of copper ions or repair sub-lethally damaged cells during subsequent liquid culture (Steuer et al 2018, Steuer et al 2020.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Copper surfaces can eliminate bacterial pathogens, viruses and fungi (Faúndez et al 2004, Wilks et Recently, using an in vitro model, we showed that the use of a copper ions treatment protocol significantly reduced MAP load in PBS (Steuer et al 2018). Later, we observed that copper ions decreased viable MAP numbers in milk in a similar way (Steuer et al 2020). However, some MAP cells apparently either tolerate the effects of copper ions or repair sub-lethally damaged cells during subsequent liquid culture (Steuer et al 2018, Steuer et al 2020.…”
Section: Introductionsupporting
confidence: 61%
“…Later, we observed that copper ions decreased viable MAP numbers in milk in a similar way (Steuer et al 2020). However, some MAP cells apparently either tolerate the effects of copper ions or repair sub-lethally damaged cells during subsequent liquid culture (Steuer et al 2018, Steuer et al 2020.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In a more novel way, we have reported that copper ions, in a liquid matrix [14,15], are highly effective against Mycobacterium avium subsp. paratuberculosis (MAP), one of the most fastidious members of the Mycobacterium genus that is also highly resistant to both physical and chemical agents [16][17][18][19] and the causative agent of paratuberculosis in ruminants [20] with zoonotic potential [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence has raised concern regarding the safety of calf milk replacer [ 14 ] and the efficacy of pasteurization [ 15 , 16 ]. For this reason, our group has explored an alternative to heat treatments, based on copper ions [ 17 , 18 ], as a means of decreasing microbial loads in raw milk. Therefore, the aim of the present study was to assess the efficacy of milk treatments to prevent MAP infection transmission to calves.…”
Section: Introductionmentioning
confidence: 99%